A novel electromagnetic mill promoted mechanochemical solid-state Suzuki–Miyaura cross-coupling reaction using ultra-low catalyst loading. Issue 15 (21st July 2022) - Li, Xin; Liu, Yunxia; Zhang, Lizhi; Dong, Yunhui; Liu, Qing; Zhang, Daopeng; Chen, Lei; Zhao, Zengdian; Liu, Hui
Abstract : The Nobel-prize-winning Suzuki–Miyaura cross-coupling (SMC) is a practical and attractive strategy for the construction of C–C bonds in both academic and industrial settings. Abstract : The Nobel-prize-winning Suzuki–Miyaura cross-coupling (SMC) is a practical and attractive strategy for the construction of C–C bonds in both academic and industrial settings. However, the development of solid-state SMC reactions remains extremely scarce. Herein, we report an electromagnetic mill (EMM) promoted solid-state SMC reaction using ultra-low palladium loading (0.05 mol%) without any liquid molecular dispersants. This protocol exhibits substantially broadened substrate scope, good functional group tolerance, efficient gram-scale synthesis and, especially, relatively high yields. The EMM conditions can suppress high aggregation of catalyst and accelerate the mixture of solid reactants, which might be the key for excellent efficiency. The utility of this strategy was exemplified in the modification of photoluminescent molecules, cross-coupling of slightly soluble compounds and synthesis of several important bioactive molecules. This solid-state EMM–SMC will be potentially developed into industrially attractive and environmentally friendly routes, and the EMM system developed in this study could unlock broad areas of chemical space for solvent-free solid-state metal-catalyzed synthesis of valuable targets in various scientific fields.